PENGEMBANGAN SENTRA BATIK SKALA HOME INDUSTRY DESA KONDANGJAJAR KABUPATEN PANGANDARAN JAWA BARAT - Agustina, Granit; Febrian, Febi; Suparyogi, Dudi (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2025)
Batik is the work of the Indonesian people which is a blend of art and technology by the ancestors of the Indonesian nation. Indonesian batik can develop to a level that is incomparable both in design or motifs as well as in the process. Kondangjajar Village, Cijulang District, as one of the areas in Pangandaran Regency, made a breakthrough by developing the art of batik craft called "Batik Kodja (Kondangjajar)" with the motif of "Marlin Fish" where the marlin fish became a trand mark in Pangandaran Regency. In its journey, the art of batik in Kondangjajar Village experienced ups and downs, especially the lack of adequate labor as batik to meet market needs, there was still a lack of knowledge about good and correct batik techniques including coloring techniques. Kondangjajar Village, Cijulang District, as one of the areas in Pangandaran Regency with the majority of the population's livelihood being fishermen, farmers, breeders and tour guides. Based on these considerations, strategic efforts through KKN-KKU activities can be used as a solution. The activity begins with the stage of program coordination to the target group, followed by training led by experienced instructors and ends with the socialization of the art of batik. The results of the activity show that the written batik training at "Batik Kodja" is able to increase the benefits and understanding of higher quality batik and coloring techniques so that in the future it can have an effect on improving the quality of Batik Kodja.